Ohmic heating of a solid-liquid food mixture in an electrically conductive package. (January 2021) - Wattanayon, Wassamon; Udompijitkul, Pathima; Kamonpatana, Pitiya
Abstract: Additive-free and nutritious packaged fruit juice (especially orange juice) is a popular beverage worldwide. Moreover, a beverage with particles and chunks provides a new experience to consumers and has become famous in Asia and Europe. The major challenge is to ensure the solid-liquid food mixture receives sufficient heat treatment, especially the solid particles, while at the same time preserving their quality. An ohmic heating system with a conductive package is an alternative method to pasteurize the food and its package as a whole, with fast and uniform heating. Our objective was to pasteurize a solid-liquid food mixture in a conductive package under ohmic heating to ensure the food was safe to consume and to preserve the vitamin C content. Orange juice with alginate particles was selected as a food model where the alginate particles with a lower electrical conductivity represented the worst case. The D- and Z-values of Escherichia coli O157:H7 DMST 12743 in alginate particles were examined and then used to calculate the pasteurization value (PU). An inoculated pack study was performed to ensure food safety while vitamin C degradation was investigated after both ohmic and conventional heating. The D-values (D) at temperatures of 50, 60, 70 and 80 °C were 19.49, 7.89, 0.64 and 0.19 min, respectively, and the calculated Z-value was 14.05 °C. For the target process with a PU value of 5D, the total ohmic heating time was 3.68 min shorter than for conventional heating (6.03 min). The inoculated pack study indicated the absence of viable microorganisms for both ohmic and conventional heating. The vitamin C content after ohmic heating was not significantly different from the untreated control, while conventional heating degraded the vitamin C by 13.58%. Thus, the ohmic heating system via the conductive package showed potential to produce safe solid-liquid foods in a shorter time, with a faster heating rate, more uniform heating and a higher retention of the vitamin C content compared to conventional heating. Highlights: Conductive package allowed electricity to pass through it to heat products inside. Solid-liquid mixture could be ohmically pasteurized within the conductive package. Ohmic heating preserved vitamin C with more rapid and uniform heating. Conductive package preserved quality by protecting foods from electrochemical reaction at electrodes. Ohmic heating with conductive package increased throughput with high energy efficiency.